The development of project risk management framework the case of United Arab Emirates - Alhashmi, Amany Mohamad Jamea Ali (2023)
The construction projects have witnessed fast development in recent decades and sustainable growth in the United Arab Emirates (UAE). Today many multinational construction companies entered the UAE construction market which imposed more pressure on local companies to improve construction performance. In most instances, construction contractors are blamed for poor project management and criticized for having limited knowledge in the application best management techniques, especially risk management. The records showed that large construction companies involved in residential projects in UAE have reported fair number of losses due improper project execution and neglecting many potential risks over a series of sub-contracts. Hence, the aim of this study is to examine the impact of risk management and skills of project managers on the performance of construction projects in UAE, as well as developing a project risk management framework. This study applied quantitative methods based on SEM to examine the relationship between the variables. SPSS and AMOS software have been used to conduct the analysis. The survey was managed in three large construction companies located in Abu Dhabi and Dubai. The total number of population equal to 1270 individuals represent project managers, civil engineers, quantity surveyors, project director, mechanical engineers, electrical engineers, ICT, architects and landscape architects. The finding shows that risk management and project manager’s skills has significant effect on project performance of construction companies. In addition, the results reveal that project manager’s skills partially mediate the relationship between risk management and project performance. The outcome of this study will help project managers assigned for construction projects to understand the main skills they must have to ensure successful completion of construction projects, whereas the practices of risk management (e.g. risk identification, risk assessment, risk response, and risk monitoring) are the basic skills that every project manager should be experienced to ensure swift completion of construction works as schedules and within the allocated budget. The implication of this study is developing a Project Risk Management Framework which can be adopted by authorities, contractors, and developers for improving the performance of projects in the UAE.